Alternative solvent systems for polycaprolactone nanowebs via electrospinning. (July 2017) - Enis, Ipek Y; Vojtech, Jakub; Sadikoglu, Telem G
In this study, polycaprolactone (PCL) was dissolved in 9:1 chloroform:ethanol mixture at 14%, 16%, 18% and 20% w/v concentrations. Then, acetic acid and formic acid were added at pre-determined amounts to 18% PCL/chloroform:ethanol solution system separately. Before production, viscosity and conductivity of prepared solutions were measured. Electrospinning technique was used for fabrication of fibrous webs. Morphology of produced webs was observed under a scanning electron microscope while fiber diameter measurements and pore analysis were realized via Image J Software System. The effect of polymer concentration and acidic solvent additions to mostly used chloroform solvent was investigated based on fiber morphology. Results indicate that the increase in polymer concentration increases the fiber diameter which leads to larger average pore area. Electrospinning of PCL with 16% to 20% polymer concentrations in chloroform:ethanol solvent system results in micro fibers. On the other hand, fiber diameter reduced from microscales to nanoscales with the addition of either acetic or formic acid. Fibers produced from PCL/chloroform:ethanol solution at 18% polymer concentration have 2.22 µm average fiber diameter, whereas 158 nm and 256 nm diameter fibers were successfully produced without a bead-like structure by 120 µl of acetic and formic acid additions to the same solution system.